A superior win and an inferior loss: new developments in Chinese bankruptcy laws and regulations. (14th July 2008) - Gu, Minkang
The long-awaited new Enterprise Bankruptcy Law (the New Bankruptcy Law) of the People's Republic of China (the PRC) was finally promulgated by the 23rd Session of the Standing Committee of the Tenth NPC and was effective on 1 June 2007. While the New Bankruptcy Law bears similar features of other bankruptcy laws around the world, it shows several new developments, which deserve further introduction. This paper will examine the Old Bankruptcy Law, as well as other regulations. In addition, new developments of the New Bankruptcy Law will be emphasised. The main intention of this paper is to comment on the newly promulgated Enterprise Bankruptcy Law. The author aims to address several remaining problems, which are supposed to be improved in the near future. The author concludes and recommends that a unified bankruptcy law must be adopted in order to deal with various debtors.